Anthropology on stage: networks of influence, sociability and prestige at the begining of Etnographic Museum of the universidad de Buenos Aires - Perazzi, Pablo (2011)
This article intends to analyse some aspects of the initial trajectory of the Ethnographic Museum —from 1904 to 1917— period characterized by the direction of archaeologist Juan B. Ambrosetti (1865-1917). The aim is to give an account of the situation of the establishment in the museological circuit locally and internationally, the inclusion of the director in the spheres of sociality, connections with collectors, amateurs, civil servants and similar institutions, networks for the exchange of favors and resources, and strategies for acquisition and training of their collections. What aims, therefore, is an understanding of the plots of power, patronage and influence around which a given intellectual space gained credibility, legitimacy and the prestige necessary to equip the discipline of the expected social and symbolic capital. The thesis supported is that, in their formative stage, anthropological disciplines were modulated and gained recognition on the basis of partnerships, generally of informal kind with institutions and agents not belonging to the community of reference.